2015
DOI: 10.1007/s10067-015-3096-6
|View full text |Cite
|
Sign up to set email alerts
|

Jumping into the deep-end: results from a pilot impact evaluation of a community-based aquatic exercise program

Abstract: This multi-center quasi-experimental pilot study aimed to evaluate changes in pain, joint stiffness, physical function, and quality of life over 12 weeks in adults with musculoskeletal conditions attending 'Waves' aquatic exercise classes. A total of 109 adults (mean age, 65.2 years; range, 24-93 years) with musculoskeletal conditions were recruited across 18 Australian community aquatic centers. The intervention is a peer-led, 45 min, weekly aquatic exercise class including aerobic, strength, flexibility, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Regular physical exercise is associated with well-being and good quality of life in the elderly (American College of Sports Medicine, 2009). One of the main findings of the present study indicates an improvement in the overall quality of life in elderly after 12 weeks of an aquatic training program, thus corroborating with studies that analysed protocols of 8 (Baena-Beato et al, 2013, 2014, 10 (Oh et al, 2015), 12 (Barker et al, 2016;Bocalini et al, 2010) and 20 (Cancela Carral & Ayán Pérez, 2008) weeks of aquatic training in the same population, showing the importance of regular practice of aquatic exercise in order to guarantee better quality of life for elderly persons. Paiva et al (2016) analysed the health factors associated with the quality of life of 3430 elderly people and observed that self-reported morbidities related to functional disability and health perception are associated with low scores of the "death and dying" and "past, present and future activities" aspects.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Regular physical exercise is associated with well-being and good quality of life in the elderly (American College of Sports Medicine, 2009). One of the main findings of the present study indicates an improvement in the overall quality of life in elderly after 12 weeks of an aquatic training program, thus corroborating with studies that analysed protocols of 8 (Baena-Beato et al, 2013, 2014, 10 (Oh et al, 2015), 12 (Barker et al, 2016;Bocalini et al, 2010) and 20 (Cancela Carral & Ayán Pérez, 2008) weeks of aquatic training in the same population, showing the importance of regular practice of aquatic exercise in order to guarantee better quality of life for elderly persons. Paiva et al (2016) analysed the health factors associated with the quality of life of 3430 elderly people and observed that self-reported morbidities related to functional disability and health perception are associated with low scores of the "death and dying" and "past, present and future activities" aspects.…”
Section: Discussionsupporting
confidence: 90%
“…Physical exercise is able to reduce the natural negative effects of aging, preventing the development of chronic-degenerative diseases and thus provide an increase in life expectancy (American College of Sports Medicine, 2009). The physical exercise performed in aquatic environment is linked to a safer practice for the elderly population, since it promotes physical and social benefits from reducing the impact on the joints, neuromuscular wear, as well as potentiating the activity in a collective environment, thus fostering an interpersonal interaction between practitioners (Barker et al, 2016;Bocalini et al, 2010;Cancela Carral and Ayán Pérez 2008;Devereux et al, 2005;Oh et al, 2015;Sato et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research using booklet diaries and comparable diary periods showed good compliance and a low dropout rate, indicating that this method is acceptable for chronic pain patients. 87 will be assessed after the final training session by means of planned focus group sessions. Small group interviews will be planned, and participants will be asked broad, open ended questions about their expectations, fulfilment of expectations, positive and negative aspects of the training and suggestions for further development of the training.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…84,87 These programmes are commonly open to a broader target population (e.g. hip and knee OA) and supervised by sport and lifestyle professionals.…”
Section: Aquatic Cycling -Advantages and Disadvantagesmentioning
confidence: 99%